Desarrollo de una propuesta de mejora en el proceso de recuperación de material no conforme en la producción de botas de PVC para la empresa Croydon Colombia S.A. (2017)
In the development of an improvement proposal in the recovery process of nonconforming material, a diagnosis of this process was made before the implementation of the project, where a set of failures were found which contribute to the generation of nonconforming product in the process, subsequently, the pre-experimental design and the experimentation of the alternatives were carried out in which the calibers in the roller mill were varied as a first step, then a Sieving analysis was carried out on the recovered triturated material where proportions of different sources of this material were varied and finally three different blends of virgin polyvinyl chloride PVC composite with the recovered material are evaluated.